GALVANIZING PROCESS IN REMOVABLE PROSTHESES-AN UP-TO-DATE OVERVIEW - Irina Gradinaru; Raluca Jipu; Loredana Hurjui; Adina Armencia; Ion Hurjui; Mihaela Mitrea; Magda-Ecaterina Antohe (Romanian Dental Association for Education, 2020)
Currently, galvanoforming made with high tech equipment is a procedure completely automated and almost completely eliminates human errors in procedure. The qualities of galvanized gold can be influenced by the gold bath and by galvanizing parameters. In the case of the electrolyte, its composition, purity and any special additives such as bath purity are of great importance. In the case of removable prostheses, the connection with the abutment teeth can be made either directly (the situation of cast dental clasps and in exceptional cases - special systems fixed adhesively), or indirectly by means of a fixed prosthesis, to special systems in general and only in some cases to clasps. A further feature of galvanoformate telescopic systems is the need for a tertiary structures (metal frame). It is fixed to the galvanoformed secondary caps with the help of a diacrylic cement and the assembly thus formed constitutes the skeleton of the prosthesis. The technology for making such restorations has certain particular stages, requiring an increased attention .